2011
DOI: 10.5761/atcs.oa.10.01653
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Thromboendarterectomy for Chronic Thromboembolic Pulmonary Hypertension : A Systematic Review

Abstract: Purpose: Pulmonary thromboendarterectomy (PTE) is a treatment option for patients with chronic thromboembolic pulmonary hypertension (CTEPH). The present systematic review was performed to assess the safety and efficacy of PTE for CTEPH. Methods: A systematic review was performed, and six electronic databases were searched for published studies from January 1999 to February 2010. All articles that presented morbidity and mortality data, survival data or preoperative and postoperative pulmonary hemodynamic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 46 publications
3
34
0
5
Order By: Relevance
“…A proportion of patients undergoing PEA still experienced pulmonary hypertension after surgery, with the rate of persistent and recurrent pulmonary hypertension following PEA reported in five European studies to be 17-31%, with a weighted average of 30% [5,10,16,17,19]. However, more recently, CANNON et al [56] reported results from a UK national cohort of 880 patients who underwent PEA for CTEPH, showing a post-surgical residual pulmonary hypertension rate of 51%.…”
Section: Cteph Incidence After Pementioning
confidence: 95%
See 1 more Smart Citation
“…A proportion of patients undergoing PEA still experienced pulmonary hypertension after surgery, with the rate of persistent and recurrent pulmonary hypertension following PEA reported in five European studies to be 17-31%, with a weighted average of 30% [5,10,16,17,19]. However, more recently, CANNON et al [56] reported results from a UK national cohort of 880 patients who underwent PEA for CTEPH, showing a post-surgical residual pulmonary hypertension rate of 51%.…”
Section: Cteph Incidence After Pementioning
confidence: 95%
“…Furthermore, despite the high success rate with PEA, it is not always curative. Among patients undergoing PEA for CTEPH, up to 51% of patients have mean pulmonary arterial pressure >25 mmHg post-PEA [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in accordance with previously published data showing substantial improvement of the pulmonary hemodynamics 1 year after PEA. However, the individual outcome differed and approximately 10-24% of patients remain symptomatic after PEA [9,38] and up to 35% presented with residual PH [12,36,39] .…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative mortality rate is remarkable and ranges from 1.3 to 24%. 16) Previously researches have been demonstrated that severely affected patients, i.e. mPAP >50 mmHg, cardiac index <2.0 l/min m 2 , pulmonary vascular resistance >1000 dynes ⋅ s ⋅ cm -5 and/or New York Heart Association class IV disease, are at high risk for postoperative bad course and mortality after PEA.…”
Section: Discussionmentioning
confidence: 99%
“…8) It is now considered to be a distal vasculopathy, in which structural changes caused by vascular remodeling and inflammation play a major role. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, the pathophysiologic mechanism of increased PVR has not been well clarified so far.…”
Section: Discussionmentioning
confidence: 99%